Economic feasibility of electric vehicles: A case study. Issue 3 (23rd November 2021) - Cheok, Quentin; Husaini, Nurul Hafizan; Nauman, Malik Muhammad
Abstract: Personal transportation is prevalent in Brunei Darussalam because of the lack of adequate public transportation. However, Brunei is not immune to the effects of climate change and as such, has launched a national policy to mitigate the impacts. As electric vehicles presently are very rare to Brunei, this article seeks to determine the total cost of ownership of internationally popular electric vehicles (EVs) and internal combustion engine vehicles (ICEVs) to put things in perspective for the Brunei market. The methodology investigated how the total cost of ownership (TCO) is affected by depreciation, interest repayment, maintenance and repair, fuel costs, taxation, and insurance premiums. We have determined that without any subsidies, predictably TCOs of EVs are higher than popular ICEVs; however, they are comparable to TCOs of European premium brands. The Tesla Model 3 has a TCO of USD 760 per month whereas a Mercedes Benz C200 has a TCO USD800 per month. The authors have suggested that a 30% subsidy on the showroom price of EVs be introduced and to improve charging infrastructure as this would be vital to governmental policy planning as Brunei seeks to increase the ownership of electric vehicles to 60% by 2035.